Student’s creative thinking based on study level, learning style, gender, and combination of the three - Edwin Musdi; Abdur Rahman As'ari; Yulyanti Harisman; Hamdani Syaputra; Kelly Angelly Hevardani (Institute of Advanced Engineering and Science, 2024)
All students from every level of education should have excellent and adequate creative thinking, but in Indonesia students’ creative thinking is still low. There are a lot of factors that affect creative thinking, such as learning styles. This study aimed to investigate the comparison of students’ creative thinking based on study level and learning styles, gender, and the combination of the three to determine which factor or type of students needs to be improved. This research uses a statistics descriptive method. The participants of this study were 38 senior high school students, 35 students of the teacher professional program (PPG), 24 undergraduate students (S1), and 12 master program students (S2). The instrument used in this study is a learning styles Learning style test to determine the student’s learning styles and creative thinking questions to classify the students. The results of this study are i) Students’ level of study does not determine their creativity level; ii) Based on gender, female is more creative than a man; iii) Based on the learning style, visual students is the best, followed by kinesthetic and auditory in order; and iv) Merdeka curriculum of Indonesia, nowadays, is essential to make the best learning process to improve students’ creative thinking.